Screening of a virtual mirror-image library of natural products. Issue 49 (20th May 2016) - Noguchi, Taro; Oishi, Shinya; Honda, Kaori; Kondoh, Yasumitsu; Saito, Tamio; Ohno, Hiroaki; Osada, Hiroyuki; Fujii, Nobutaka
Abstract : A novel approach for screening an unexplored mirror-image library of chiral natural products has been developed by usingd -protein technology. Abstract : We established a facile access to an unexplored mirror-image library of chiral natural product derivatives usingd -protein technology. In this process, two chemical syntheses of mirror-image substances including a target protein and hit compound(s) allow the lead discovery from a virtual mirror-image library without the synthesis of numerous mirror-image compounds.